Quantum mechanical calculations of state-to-state cross sections and rate constants for the F plus DCl ? Cl plus DF reaction - Bulut, Niyazi; Klos, Jacek; Roncero, Octavio (Amer Inst Physics, 2015)
We present accurate state-to-state quantum wave packet calculations of integral cross sections and rate constants for the title reaction. Calculations are carried out on the best available ground 1(2)A' global adiabatic potential energy surface of Deskevich et al. [J. Chem. Phys. 124, 224303 (2006)]. Converged state-to-state reaction cross sections have been calculated for collision energies up to 0.5 eV and different initial rotational and vibrational excitations, DCl(v = 0, j = 0 - 1; v = 1, j = 0). Also, initial-state resolved rate constants of the title reaction have been calculated in a temperature range of 100-400 K. It is found that the initial rotational excitation of the DCl molecule does not enhance reactivity, in contract to the reaction with the isotopologue HCl in which initial rotational excitation produces an important enhancement. These differences between the isotopologue reactions are analyzed in detail and attributed to the presence of resonances for HCl(v = 0, j), absent in the case of DCl(v = 0, j). For vibrational excited DCl(v = 1, j), however, the reaction cross section increases noticeably, what is also explained by another resonance. (C) 2015 AIP Publishing LLC.
Keywords: Potential-Energy Surface; Oppenheimer-Type Separation; Deuterium-Isotope Variants; Wave-Packet; Reaction Probabilities; Hydrogen Abstraction; Dynamics; Scattering; Hcl; Hf